Teaching Empirically Supported Substance Use Interventions in Social Work: Navigating Instructional Methods and Accreditation Standards. (1st May 2018) - Smith, Douglas C.; Egizio, Lori L.; Bennett, Kyle; Windsor, Liliane C.; Clary, Kelly
ABSTRACT: Changes to the Council on Social Work Education's Educational Policy and Accreditation Standards encourage students to develop competencies in empirically supported treatment models. Although there is discretion in how educators build such competencies, studies on training suggest combining didactic and interactive classroom techniques with supervised practice experiences would produce the best training outcomes. Screening, brief intervention, and referral to treatment (SBIRT) has become a valuable empirically supported treatment model for addressing substance use. Because social workers work with patients in diverse settings, empirically supported treatment models such as SBIRT are useful for students to practice as part of their course work and internship experiences. This article explains a university's training model, demonstrates how it addresses social work competencies, and presents preliminary outcomes.